Can cognitive performance predict physical fitness and academic achievement one year later? - Gil-Espinosa, Francisco Javier; Chillón, Palma; Cadenas-Sánchez, Cristina (Profith. Universidad de Granada, 2017)
Previous studies have shown that physical activity, fitness and academic achievement might predict cognitive performance later in life . However, to the best of our knowledge, there are no studies examining the inverse relationship, that is, whether cognition may predict fitness and academic achievement in adolescents one year later . Therefore, the aim of this study was to examine the associations between cognitive performance and physical fitness and academic achievement one year later .
Keywords: Rendimiento académico; Cognitive perfornance; Academic achievement; Fitness